2009
DOI: 10.1016/j.ijpara.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mutation in the para-sodium channel gene of the cattle tick Rhipicephalus (Boophilus) microplus associated with resistance to synthetic pyrethroid acaricides

Abstract: Accepted ManuscriptIdentification of a mutation in the para sodium channel gene of the cattle tick Rhipicephalus (Boophilus) microplus associated with resistance to synthetic pyrethroid acaricides This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
86
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 17 publications
10
86
1
2
Order By: Relevance
“…Molecular studies did not find the Domain III sodium channel mutation of Guerrero et al (2001), thus suggesting a novel sodium channel mutation was present in the Santa Luiza strain. We have now confirmed that Santa Luiza contains the Morgan et al (2009) Domain II mutation and this likely leads to the permethrin resistance phenotype of this Brazilian strain (F. GUERRERO, unpublished data).…”
Section: Pyrethroid Resistancesupporting
confidence: 67%
See 4 more Smart Citations
“…Molecular studies did not find the Domain III sodium channel mutation of Guerrero et al (2001), thus suggesting a novel sodium channel mutation was present in the Santa Luiza strain. We have now confirmed that Santa Luiza contains the Morgan et al (2009) Domain II mutation and this likely leads to the permethrin resistance phenotype of this Brazilian strain (F. GUERRERO, unpublished data).…”
Section: Pyrethroid Resistancesupporting
confidence: 67%
“…The Domain II mutations are reported to convey lesser levels of resistance. The leucine to isoleucine change reported by Morgan et al (2009) conveys moderate levels (100-400-fold estimates) of resistance to permethrin, cypermethrin, and flumethrin, while the glycine to valine change was flumethrin resistance-specific and seemed to provide lower levels of resistance (JONSSON et al, 2010). Thus there are at least three target site mechanisms for pyrethroid resistance in R.…”
Section: Pyrethroid Resistancementioning
confidence: 99%
See 3 more Smart Citations